Multi-mode absorption spectroscopy of oxygen for measurement of concentration, temperature and pressure - Arita, Y; Stevens, R; Ewart, P (2008)
The use of multi-mode absorption spectroscopy (MUMAS) to detect multiple transitions in the A-band b(1)Sigma(g) (+)-X-3 Sigma(-)(g) of molecular oxygen is reported. The modelling of MUMAS signatures and the procedure for fitting such model signatures to experimental data obtained using a multi-mode diode laser is described. The technique is shown to allow accurate and precise measurement of concentration, temperature over the range 300 to 500 K and of pressure over the range 0.2 to 1 bar. Extension of the technique to other ranges of temperature and pressure and to other species is discussed.